Worker, Work, and Work Dynamics: The Role of Multi-skilled, Proactive, and Customer-Focused Staff. - FAZAL HALEEM; SYED TANVEER HUSSAIN SHAH (Journal of Business & Tourism, 2021)
In today‟s world, organizations are increasingly becoming decentralized, facing fastpaced change, higher demands of innovation, greater operational uncertainty, increasingly blurred careers (Bindl and Parker, 2010) and the changing and volatile demands of products and services that bring some serious changes in work place and in the way products and services are produced ( Kim and Seoul, 2003.). In order to better cope with such problems firms need individuals who have wide range of skills to perform various tasks, understand and have knowledge about the overall production process and the business, are good at problem solving, proactive, propose and influence changes in organizational routines, take initiative to solve problems immediately without the help of others (Kim and Seoul, 2003; Gerhardt et al. 2009). The research mainly critically reviews literature on importance of multi-skilled, pro-active, and customer focused employees. The research concludes that it is realty that an organization needs multiskilled, proactive and customer focused staff to be successful. The paper contributes to the literature and offers implications for HR officers that why an organization needs multi-skilled, proactive and customer-focused staff and how does it contribute in achieving organizational goals and objectives.